(untitled) (Progressive Agriculture, 2014)
The study was conducted in rural areas of Mymensingh district during March to April 2007. Seventy two households were interviewed and respondents were grouped in three categories: low, medium and high income group to identify the respondents socio-economic condition, total waste production, processing, utilization and preservation methods of waste. The total organic waste production was unequally proportionate areas among low, medium and high income group. Waste generation was also depending on family size and family income. Smaller family generated less amount of waste while larger family generated huge wastes. High income contributes to generate more wastes. The characteristics such as family size and family income of the respondents had positive and significant relationships with their waste generation. Waste use as many purpose such as manure, fuel, landfill etc. A significant amount of waste generated from domestic animal, specially cowdung have been using as fuel purpose. Only 2.78% respondents used cowdung as compost in their crop field due to less number of domestic animals and scarcity of fuel wood. But 27.78% respondents were not used it for any of those purposes. Besides these ashes, kitchen waste, feed wastage etc. are used as manure and landfill purpose. Respondents had no systematic planning in all spheres of production, processing and utilization of organic waste. The respondents were disposing their solid waste at various times. As a result improper processing and preservation of wastes have been occurring serious air and water pollution. DOI: http://dx.doi.org/10.3329/pa.v18i2.18383 Progress. Agric. 18(2): 247 - 254, 2007